The corporate social responsibility of the media sector of the city of Puno - Yucra Mamani, Yudi Janeh (2016)
The social responsibility of the communication means from Puno City, is the subject of this research. A little-known and researched, for which a survey to find out how assume corporate social responsibility (CSR) sector of the media in Puno, how we understand and the actions taken in this regard was administered and determine if they have an agenda of issues of social responsibility; Interviews were also conducted with the managers of the media under study, whose results reinforce and contrast the information obtained through the questionnaire questions. The research is descriptive - comparative, and revealed that corporate social responsibility of the media Puno is taken partly as such ignorance in this regard is still evident, although there are common practices in corporate social responsibility (CSR) to all specific sectors and media sector, unresponsive to work planning. CSR's bound to work for social investment and philanthropy. It is also evident that the media understand CSR from a variety; CSR actions shown through campaigns, programs, partnerships, donations, events like forums and debates, and specific actions own the media through journalistic productions and communications sector; likewise there is a lack of an agenda of planned social responsibility issues. An important finding was to determine the formation of a "media collective" formed on the initiative of some media, this effort becomes a first experience of true social responsibility, so it is imperative to strengthen and ensure their permanence.